Towards the use of vector based GP to predict physiological time series - Azzali, Irene (2020)
Azzali, I., Vanneschi, L., Bakurov, I., Silva, S., Ivaldi, M., & Giacobini, M. (2020). Towards the use of vector based GP to predict physiological time series. Applied Soft Computing Journal, 89(April), [106097]. https://doi.org/10.1016/j.asoc.2020.106097-----------------------------------------------------------------This work was partially supported by FCT, Portugal, through funding of LASIGE Research Unit (UIDB/00408/2020) and projects INTERPHENO (PTDC/ASP-PLA/28726/2017), PERSEIDS (PTDC/EMS -SIS/0642/2014), OPTOX (PTDC/CTA-AMB/30056/2017), BINDER (PTDC/CCI-INF/29168/2017), AICE (DSAIPA/DS/0113/2019), GADgET (DSAIPA/DS/0022/2018), and PREDICT (PTDC/CCI-CIF/29877/2017). This study was also supported by Ministero dell'Istruzione, dell'Universita e della Ricerca (MIUR) under the programme "Dipartimenti di Eccellenza ex L.232/2016'' to the Department of Veterinary Science, University of Turin.